Radical transformation and the limits of law - Shai, Isaac (Acta Academica: Critical views on society, culture and politics, 2019)
This article evaluates the capacity of law and thus transformative constitutionalism to bring about radical transformation in South Africa. It is argued that the structural limits of law constrain the capacity of law and constitutionalism to bring about radical transformation in South Africa. Niklas Luhmann’s systems theoretical approach is used to explore the limits of law. The article cautions against the unbridled bestowing of the reconstruction of South Africa on legal and constitutional mechanisms.